2022
DOI: 10.3390/cells11030416
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Protein Variants Driving Atrial Fibrillation: Potential Mechanisms of Action

Abstract: The most common clinical tachyarrhythmia, atrial fibrillation (AF), is present in 1–2% of the population. Although common risk factors, including hypertension, diabetes, and obesity, frequently underlie AF onset, it has been recognized that in 15% of the AF population, AF is familial. In these families, genome and exome sequencing techniques identified variants in the non-coding genome (i.e., variant regulatory elements), genes encoding ion channels, as well as genes encoding cytoskeletal (-associated) protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 131 publications
0
9
0
1
Order By: Relevance
“…With the incidence of AF increasing over the years, it is crucial to explore the various risk factors of AF. Previous studies have demonstrated the significant contribution of cytoskeletal protein variants and calcium ions in the development of AF from a molecular biological perspective [ 44 , 45 , 46 ]. And in the present research, we focus on the role of a higher BWM in the onset of AF.…”
Section: Discussionmentioning
confidence: 99%
“…With the incidence of AF increasing over the years, it is crucial to explore the various risk factors of AF. Previous studies have demonstrated the significant contribution of cytoskeletal protein variants and calcium ions in the development of AF from a molecular biological perspective [ 44 , 45 , 46 ]. And in the present research, we focus on the role of a higher BWM in the onset of AF.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MYH6 encodes the α-subunit of myosin heavy chain predominantly expressed in atrium. Myosin, an ATPase cellular motor protein whose heavy chain subunit is a main component (31,32). MYL4 is a chamberspecific expression restricted to the atria, which encodes atrial Light Chain-1, a key sarcomeric component.…”
Section: Pathophysiological Mechanisms Of Af Remodelling In Hcmmentioning
confidence: 99%
“…The overexpression of MYH6 in HL-1 and isolated rat atrial cardiomyocytes results in sarcomere impairment, electrophysiological abnormalities, and a slower conduction velocity, suggesting the potential role of MYH6 gene variants in atrial structure and function. Comparable pathways may play a role in mutant MYH6-induced AF ( 31 , 32 ). MYL4 is a chamber-specific expression restricted to the atria, which encodes atrial Light Chain-1, a key sarcomeric component.…”
Section: Pathophysiological Mechanisms Of Af Remodelling In Hcmmentioning
confidence: 99%
“…The clinical spectrum of desminopathies is broad and even within the same family different types of cardiomyopathies may result [15]. Ventricular and atrial arrhythmias are frequently observed in patients with desminopathies [16][17][18][19] leading in some cases to cardiac arrest or even sudden cardiac death [20,21].…”
Section: Introductionmentioning
confidence: 99%